2014
DOI: 10.1523/jneurosci.1336-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Depth in Natural Images Reflects Encoding of Low-Level Luminance Statistics

Abstract: Sighted animals must survive in an environment that is diverse yet highly structured. Neural-coding models predict that the visual system should allocate its computational resources to exploit regularities in the environment, and that this allocation should facilitate perceptual judgments. Here we use three approaches (natural scenes statistical analysis, a reanalysis of single-unit data from alert behaving macaque, and a behavioral experiment in humans) to address the question of how the visual system maximiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
6
20
0
Order By: Relevance
“…Confirming and expanding on previous results, we found that bright and dark visual features are distributed asymmetrically in terms of their contrast levels and relative depths [ 12 , 15 , 26 ]. In addition, we found that the spatial frequency content of natural scenes differs substantially between brights and darks, with a higher dark bias at low spatial frequencies.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Confirming and expanding on previous results, we found that bright and dark visual features are distributed asymmetrically in terms of their contrast levels and relative depths [ 12 , 15 , 26 ]. In addition, we found that the spatial frequency content of natural scenes differs substantially between brights and darks, with a higher dark bias at low spatial frequencies.…”
Section: Introductionsupporting
confidence: 90%
“…This dark/bright dichotomy, however, has been largely overlooked in the study of natural scene statistics. There are three relevant observations that motivate our analysis: natural scenes contain more dark visual contrast [ 20 , 24 , 25 ], this dark bias increases at higher contrast levels [ 15 ], and dark visual contrasts also tend to be associated with farther relative depths [ 12 , 19 , 26 ]. These observations led us to hypothesize that the bright and dark visual features of natural images may differ along other dimensions as well.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of results is consistent with a Bbrighter is closer^heuristic. This heuristic mirrors the relationship between contrast and depth in natural scenes, sometimes known as proximity-luminance covariance (Coules, 1955;Schwartz & Sperling, 1983;Dosher, Sperling, & Wurst, 1986) and recently has been shown to bias observer reports of perceived depth in natural images (Cooper & Norcia, 2014). Thus, in the context of our study, observers may be influenced by a prior expectation of target position in addition to any prior expectations of target motion, especially in cases where sensory uncertainty is already high.…”
Section: Discussionsupporting
confidence: 51%
“…That is, cells with near or far disparities tend to be sensitive to local luminance maxima and minima respectively (Samonds et al, 2012). These effects have been reanalyzed and confirmed by Cooper and Norcia (2014) who also reported on a psychophysical study. Using natural images along with registered depth maps, they showed the perception of 3-D depth could be enhanced or diminished by biasing the image intensities toward a negative or positive depth-luminance covariance, respectively.…”
Section: Introductionmentioning
confidence: 62%